No evidence of benefit for laminar flow in theatre for sling-assisted, implant-based breast reconstruction. Issue 5 (October 2021) - Barber, Matthew D.; Young, Oliver; Kulkarni, Dhananjay; Young, Ian; Saleem, Talha Bin; Fernandez, Teresa; Revie, Erica; Dixon, J. Michael
Abstract: Introduction: Recent years have seen a large increase in the proportion and number of sling-assisted, implant-based breast reconstructions. These are associated with significant rates of loss of the reconstruction. Various methods have been suggested to reduce this loss rate. One such method is the use of operating theatres with laminar flow. The majority of cases of sling-assisted, implant-based breast reconstruction in south-east Scotland are performed in two adjacent theatres, one with laminar flow and one without. This provided the opportunity to assess whether there was any difference in outcome potentially attributable to laminar flow. Methods: Patients undergoing sling-assisted, implant-based breast reconstruction between August 2013 and December 2018 were studied with follow up for at least 6 months. Results: 307 patients underwent a total of 470 procedures. 247 procedures were performed with laminar flow and 223 without. There was no difference in the indications for mastectomy, incision used or rates of smoking or radiotherapy between the two groups. Implant loss occurred in 15.8% of procedures with laminar flow and 14.3% of those without (p = 0.66). Wound problems occurred in 27.5% of procedures with laminar flow and 27.8% of those without ( p  = 0.97). There was no significant difference in loss rates between surgeons, mastectomy indication, sling materials or with chemotherapy use. Increased loss rates were observed in smokers, with radiotherapy, with incisions other than transverse, with larger breasts and with increasing patient weight. Conclusion: This study finds no evidence of benefit for laminar flow in theatre for sling-assisted, implant-based breast reconstruction. Highlights: Laminar flow in theatre does not appear to reduce implant loss rate. Implant loss was associated with smoking, radiotherapy, weight and breast size. Care is required in patient selection for implant-based breast reconstruction.